Sex work, multi-agency governance and industries of protection: towards an increased recognition and resistance of the carceral - Sam Hanks (Justice, Power and Resistance, 2024)
This article focuses on sex work governance within multi-agency partnerships and initiatives in Wales. By engaging with notions of carceral humanism, this article seeks to make tangible the ways in which multi-agency partnerships co-opt and assimilate criminologists, activists, third sector and community organisations so that partisan commitments to advancing sex workers rights are transformed to bipartisan support for non-competing carceral frameworks and solutions. It argues there is a process of carceral bifurcation that enables narratives of safeguarding and sex work to be utilised to strengthen non-competing carceral conceptualisations of, and solutions to sex work.